UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN METODE PEMBELAJARAN DARING MELALUI APLIKASI GENIUS INDONESIA DI MASA PANDEMI COVID-19 - Villa Santika (Jurnal Analisis Pendidikan Sosial, 2023)
This research aims to find out the increasing academic achievement of students learning in online learning method through the Genius Indonesia Application in Business Planning subjects. This study is a research action study with research subjects of grade X students BDP SMK Wikarya Karanganyar as many as 42 students. This research was conducted 2 cycles, added pre-cycle, each cycle consisting of 4 meetings. At each meeting consists of 4 stages namely planning, implementation, observation, and reflection. Data collection techniques used include observations and interviews in implementation stage. Based on results of the study, in pre-cycle obtained a cognitive aspects is 26.19%, psychomotor aspects is 40.48%, and affective aspects is 35.71% with not target categories. While in cycle I, the cognitive aspects is 61.90%, psychomotor aspects is 61.90% with not target categories but affective aspects is increase up to 78.57% with target categories. Finally, in cycle II, the cognitive aspects is 88.10%, psychomotor aspects is 78.57%, and affective aspects is 92.86% where all the aspects with the category were more than the target of 70.00%. Thus it can be concluded that through the Genius Indonesia Application can increase the academic achievement of grade X students BDP of SMA SMK Wikarya Karanganyar towards Business Planning lessons, in online learning during the covid-19 pandemic.